2022
DOI: 10.55544/jrasb.1.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibiotic Resistance Pattern at the Medical Services Administration Hospital in Khartoum, Sudan, 2021

Abstract: The number of antibiotics available is limited and does not cover the growing antibiotic resistance challenge. Misuse and overuse of antibiotics act as factors that help in improving and increasing the problem of resistance to those currently being prescribed by doctors. The study was carried out at the Medical Services Administration Hospital (MSAH) in Khartoum, Sudan to investigate the antibiotic resistance pattern for the period between Dec. 2020 and Jan. 2022. The results showed that, in a total of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 46 Further, another study reported that the antibiotic misuse found in their study was consistent with the city profile of antibiotic resistance. 13 In Sudan, O. Abdellatif et al 47 has reported that some bacteria including Klebsiella pneumonia, Staphylococcus aureus , and E. coli were highly resistant to cefixime by more than 90% of the total cases of the study. Also, a study conducted in Khartoum state has documented an increased resistance of the isolated bacteria to penicillin, cephalosporins, macrolide, and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 94%
“… 46 Further, another study reported that the antibiotic misuse found in their study was consistent with the city profile of antibiotic resistance. 13 In Sudan, O. Abdellatif et al 47 has reported that some bacteria including Klebsiella pneumonia, Staphylococcus aureus , and E. coli were highly resistant to cefixime by more than 90% of the total cases of the study. Also, a study conducted in Khartoum state has documented an increased resistance of the isolated bacteria to penicillin, cephalosporins, macrolide, and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 94%
“…In Sudan, there was a significant resistance rate to most antibiotics frequently used in hospitals. 9 However, extensive use of both broad-and narrow-spectrum antibiotics in ICU may develop resistant strains of bacteria and other pathogens. 10 Antibiotic resistance within the ICU is very high because nosocomial infections require multiple antimicrobial therapies.…”
Section: Introductionmentioning
confidence: 99%